Estudio de factibilidad para la creación del Instituto Tecnológico Superior Particular Empresarial Latacunga. - Cajas Peralvo, Juan Francisco (2020)
This project searches to identify the feasibility to open the Latacunga Private Business Technological Institute in Latacunga city, Cotopaxi province, considering that education is a human right, which should be dealt to all its levels. This investigation focuses its theoretical basis in the problems’ conceptual analysis which is affecting higher education and access to it, as well as identified in Latacunga Private Business Technological Institute. The market study allows to determine that there is a great deal of unmet demand, since the offer that there is currently in the country. It does not cover the school population and non-school demand. Thus, this technical study established the main characteristics at ITSPEL service. As well also, it determines the facilities location, installed capacity and distribution of the same. The ITSPEL can guide its academic proposal with modern and ergonomic facilities in conjunction with the academic teaching. What is more, it is able to ensure the quality and excellence service. The administrative section at ITSPEL shows the mission, vision, values. As well as, it identifies staff functions strategic objectives for the optimal functioning. On the other hand, in the financial study analyzing the costs and expenses have been structured financial statements to later evaluate them and show their viability. For everything, this was described and obtained that it can be determined that the feasibility study for Latacunga Private Business Technological Institute`s creation, it is viable.